The Digital Economy Anniversary Edition (2014) Rethinking Promise and Peril in the Age of Networked Intelligence - เหลี่ยมปรีชา, วศิน (Journal of Business, Innovation and Sustainability (JBIS), 2016)
บทวิจารณ์หนังสือ (Book Review) The Digital Economy Anniversary Edition (2014) Rethinking Promise and Peril in the Age of Networked Intelligence Download DOI: http://dx.doi.org/10.14456/becj.2016.39